Developing a Method for Evaluating the Comprehension of My Examples Using Spinning Whel by Applying to Students at Al- Qodiri Islamic Middle School Jember - Siti Alfiatul Jannah; Faisol Nasar Bin Madi; Abdur Rosid (Institut Dirosat Islamiyah Al-Amien Prenduan, 2024)
As we know, assessment is always used to measure students' abilities in all subjects. However, most schools use paper-based media to assess students' abilities, which allows students to cheat on each other. Therefore, the researcher aims to develop a spinning wheel-based assessment media for the Amtsilati textbook. The objectives of this research are 1) to describe the development of the student comprehension assessment towards